3D concrete printing of eco-friendly geopolymer containing brick waste. (April 2023) - Pasupathy, Kirubajiny; Ramakrishnan, Sayanthan; Sanjayan, Jay
Abstract: This study investigates alkali-activated brick waste powder as the binder for developing 3D printable geopolymer mixes. The brick waste was used as a partial replacement to fly ash in geopolymer binders. The effect of brick waste content on the fresh properties of printable mixes, such as flow, setting time and rheological properties were investigated. Besides, the hardened properties of 3D printed brick waste geopolymer were evaluated with the varying brick waste content in the mix. The test results demonstrated that the fresh properties of 3D printable mixes were improved with the brick waste content in the mix. Compared to the control mix, the mixes containing brick waste displayed high yield strength and apparent viscosity at an early age. On the contrary, the hardened properties of compressive strength and interlayer strength of 3D printed concrete specimens were decreased with the high brick waste content; however, the incorporation of brick waste for up to 10% has enhanced the hardened properties. Finally, the sustainability assessment of brick waste geopolymer studied with embodied energy and carbon emission calculations reveals the proposed geopolymer concrete could reduce the embodied energy and carbon emission by up to 60–80%, compared to OPC concrete.